Investigation of lipid digestion by fungal and porcine lipase supplements for severe pancreatic insufficiency using the in vitro dynamic TIM model - Tânia Martins Garcia; Ioannis Vrasidas; Alexander Iphoefer; Bartosz.lipowicz Lipowicz (University of Huddersfield Press, 2023)
Exocrine pancreatic insufficiency (EPI) is caused by insufficient secretion or limited activity of pancreatic enzymes, especially lipase. Chronic pancreatitis (CP) is the most common EPI disease. CP patients suffer from gastrointestinal symptoms such as diarrhea, abdominal pain, and decreased uptake of nutrients as a consequence of inadequate food digestion. To improve their nutritional status, pancreatic enzyme supplements can be orally administered, known as pancreatic enzyme replacement therapy (PERT). PERT is commonly based on oral porcine preparations, despite their pH sensitivity which results in a limited timeframe for optimal activity. Instead, fungal enzymes could be used to prolong enzyme activity duration, since they are active over a wide pH range. The performance of fungal enzymes was compared to porcine enzymes by measuring total fatty acids under severe pancreatic insufficiency conditions in the tiny-TIMsg dynamic in vitro gastrointestinal model. Administration of 14.000 fungal lipase units (Nortase) led to similar lipid digestion compared to 20.000 porcine lipase units (Kreon and Pangrol). Additionally, opening the Nortase capsules had no negative effect on fungal lipase activity. This work demonstrates that fungal lipases, administered as capsules or powder, can be used as an alternative treatment for EPI patients.